IMPLIKASI PENDIDIKAN MULTIKULTURAL - M. Syamil Nurizzi; Hidayat; M. Husnul Walidain (CV Putra Publisher, 2022)
Multiculturalism is a term that is relatively new in today's global discourse. In its development, multiculturalism is nothing more than a term that perfects the previous idea, namely pluralism. Multicultural in the perspective of the Indonesian nation is not something surprising. This is because the character and personality of the Indonesian people are accustomed to the extraordinary diversity of this archipelago. Multiculture is not something new because Islamic doctrine and civilization have presented how Muslims with the guidance of revelation should behave. The diversity of human beings is seen as the cause of suffering and misery. Conflicts and wars that exist are seen as a result of this diversity which creates a siltation of humanity's attitude towards it. So experts consider that multicultural awareness must be instilled and become part of human awareness in various aspects of life. To instill this awareness requires an effective method. Education is ultimately seen as a solution to this. The nation-state of Indonesia is full of diversity, be it ethnic, religious, cultural, ethnic/racial, regional, and so on, so understanding and applying multicultural values is a must. It is very urgent to include multicultural education in the curriculum, at least